Struktur, Fungsi, dan Nilai-nilai Pendidikan dalam Ungkapan Kepercayaan Rakyat Batu Hampar Pesisir Selatan - Gusmayenti, Nova; R., Syahrul; Abdurahman, Abdurahman (Universitas Negeri Padang, 2013)
The purpose of research are the first, describe the structure, meaning, function and educational value expression believe Batu Hampar society, and the last implications for learning Indonesian. The data of this study was sixty-expression. The data source of this study is that oral sources delivered directly by the informant as the original speakers. Data collected using methods and techniques of recording and see my technique as advanced techniques. The findings of the study are two-part structure found fifty-seven expressions, the three parts are found three expressions, meanings found sixty-expression. Functions as an expression of people's expressions educate numbered eleven, twelve tga reminds found expression, found one telling phrase, mengibur found two expressions, and prohibits discovered thirty three expressions. Educational value as an expression of people's social value of education found nineteen expression, the value found three expressions of religious education, physical education values ​​found twelve expressions, and the value of family welfare education found twenty-seven expressions.